V407 Cyg and RS Oph - comparison of two exotic variables - Drozd, K.; Swierczynski, E.; Ragan, E.; Buil, C. (Advances in Astronomy and Space Physics, 2013)
V407 Cygni and RS Ophiuchi are two similar but unique objects. It can be said that they each belong to an individual type of stars. During their quiet state they seem to be symbiotic stars. However, both stars have previously displayed nova-like outbursts. We would like to take a closer look at these two unique objects, and to compare them. We presented spectroscopic and photometric observations of V407 Cyg and RS Oph obtained throughout the period from 2006 until 2013. Our data show the di erent activity stages connected with the two components of these binary systems. Multicolour photometry and spectra obtained in a wide frequency range are utilized to understand the behaviour of such extremely binaries.